ASSOCIAÇÃO DE GLYPHOSATE E OUTROS HERBICIDAS COM ÁCIDO SALICÍLICO NA OCORRÊNCIA DE OÍDIO, NA ROTA DO ÁCIDO CHIQUIMICO E COMPORTAMENTO NA SOJA RR® - SILVA, ANDRÉ AUGUSTO PAZINATO DA (2016)
The research was performed with the objective of evaluating glyphosate + lactofen association and other herbicides with salicylic acid in occurrence of oidium, on the shikimic acid route and behavior of sobybean RR™ crop in Guarapuava region, Parana State. Four experiments were conducted in field conditions at Guarapuava County and at laboratories belonging to Universidade Estadual do Centro-Oeste - (UNICENTRO) and Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP/FCA), during 2013-14 and 2013-15 agricultural years. Treatments were disposed in randomized complete blocks, with 16 treatments and five replications. In the experiments the following treatments were used (g i.a. ha-1): glyphosate (RR) (960), sodium salicylate (AS) (256 ), lactofen (30; 60 and 120), RR + lactofen + AS (960 + 30 + 256; 960 + 60 + 256 and 960 + 120 + 256), RR + chlorimuron (960 + 12,5), RR + chlorimuron + SS (960 + 12,5 + 256), RR + cloransulan (960 + 30,2), RR + cloransulan + AS (960 + 30,2 + 256), RR + bentazon (960 + 480), RR + bentazon + AS (960 + 480 + 256) and a check without application. In studies conducted in field conditions results indicate that injuries caused by glyphosate + lactofen + salicylic acid associations were superior than isolated lactofen, being the increased lactofen dose responsible for increasing the intensity of phytotoxic effects on BMX Apollo RR (exp. 1) and BMX Vanguarda IPRO cultivars (exp. 2). Glyphosate + chlorimuron and glyphosate + cloransulan, associated to salicylic acid, showed lower toxic effect on soybean crop about not adding salicylic acid in the tank mixture. Lactofen isolated and glyphosate + lactofen + salicylic acid and treatments involving glyphosate herbicide associated to chlorimuron, cloransulam and bentazon in the presence or absence of salicylic acid reduced soybean plants initial chlorophyll, as well as promoted suppression of crop height, with better performance for BMX Apolo RR cultivar. Lactofen (120 g ha-1) and RR + lactofen + AS (960 + 120 + 320 g ha-1) reduced significatively the following characteristics number of pods per plant, grains per pod, weight of a 100 seeds and grain yield, did not showing viability for using soybean studied cultivars. All studied treatments significantly reduced the incidence and severity of soybean oidium, being a complementary option for diseases management. In general, treatments application alter the production of compounds metabolites of shikimic acid route, in both old leaves and in new leaves (new shoots). In laboratories condictions it was only possible to detect glyphosate and bentazon herbicides in applied and unapplied leaves of soybean RR® crop, indicating that other herbicides showed fast metabolism (≤ 14 days). Results indicate occur direct dependency of soybean RR® cultivar in the dynamics of glyphosate translocation of leaves applied to theones unapplied, with this effect reduced for the association of glyphosate + lactofen + salicylic acid. The additions of recovered SS in leaves of soybean RR® cultivars were about 0.9 to 1.7 times in relation to the check when submitted to applications of glyphosate, lactofen, glyphosate, glyphosate + chlorimurom + cloransulam and glyphosate + bentazon. Associations of glyphosate with lactofen and chlorimurom, both with SS, favored the metabolizing of AMPA in soybean leaves. The application of glyphosate and glyphosate + salicylic acid caused significant increments in shikimic acid concentration, as well as in the synthesis of chain aromatic amino acids and and branched in soybean RR® leaves, as well as decreases of these compounds when used lactofen and glyphosate+lactofen+salicylic acid.